2023
DOI: 10.3389/fendo.2022.1034614
|View full text |Cite
|
Sign up to set email alerts
|

Circulating estradiol and its biologically active metabolites in endometriosis and in relation to pain symptoms

Abstract: ObjectivesEndometriosis (EM) is an estrogen-dominant inflammatory disease linked to infertility that affects women of reproductive age. EM lesions respond to hormonal signals that regulate uterine tissue growth and trigger inflammation and pain. The objective of this study was to evaluate whether estradiol (E2) and its biologically active metabolites are differentially associated with EM given their estrogenic and non-estrogenic actions including proliferative and inflammatory properties.DesignWe performed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Oxidative stress triggers IL-33 secretion during airway inflammation [ 30 ]. Similarly, ectopic endometriotic cells also survive in oxidative stress, hypoxic environments, transforming growth factor-β1 (TGF-β1) [ 31 ], and estradiol (E 2 ) [ 32 ] have been recognized as essential factors in EMs development. Therefore, we explored whether these factors could trigger IL-33 secretion by ESCs.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress triggers IL-33 secretion during airway inflammation [ 30 ]. Similarly, ectopic endometriotic cells also survive in oxidative stress, hypoxic environments, transforming growth factor-β1 (TGF-β1) [ 31 ], and estradiol (E 2 ) [ 32 ] have been recognized as essential factors in EMs development. Therefore, we explored whether these factors could trigger IL-33 secretion by ESCs.…”
Section: Resultsmentioning
confidence: 99%
“…These ndings can be attributed to CS increasing the hepatic metabolism of oral estrogens, thus preventing the body from using drug-derived estrogens by converting them to forms that are less active. In addition, the 2hydroxylation of estradiol results in the production of metabolites that have been associated with endometriosis and pain [25].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen itself stimulates the growth of endometriosis, while progesterone inhibits the occurrence of endometriosis. Therefore, it can be concluded that progesterone resistance in endometriosis leads to increasing growth of endometrial tissue [ 12 , 13 ]. Furthermore, progesterone resistance and the uncontrolled increase of estradiol (E2) levels in endometrial tissue initiate the increase of one angiogenic factor, namely VEGF, that causes angiogenesis and neurogenesis in endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone resistance and the uncontrolled increase of the estradiol level in endometrial tissue also initiates an increase of vascular endothelial growth factor (VEGF) that causes angiogenesis and neurogenesis in endometriosis. All of the above mechanisms lead to the development and progression of endometriosis [ 4 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%